(untitled) (Revista Educação, Artes e Inclusão, 2021)
This article aims to discuss the theoretical framework that underlies the actions developed in the care of NAE - Educational Accessibility Center based on the analysis of the guiding documents that legitimize it, as well as the instruments used to record the educational specificities of students. catered for, namely, Target Audience of Special Education- PAEE (people with disabilities, global developmental disorders, high skills / giftedness) and with specific educational needs-SEN. Methodologically, we use the theoretical analysis anchored in Minayo (2013) centered on the notion of theme that spells out a range of relationships graphically presented in words and / or expressions specifically studying the case of the State University and Santa Catarina-Udesc. For that, two categories were used: Biomedical Model and Social Model of Disability that, through reference units, allowed the analysis of the chosen objects. This investigation clarified the coexistence of both categories in 57% of the objects investigated and pointed to weaknesses that may, to some extent, compromise the results obtained in welcoming the NAE target audience.